2022
DOI: 10.1158/0008-5472.can-21-3376
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gain-of-Function Activity of Three p53 Hotspot Mutants In Vivo

Abstract: The majority of TP53 missense mutations identified in cancer patients are in the DNA-binding domain and are characterized as either structural or contact mutations. These missense mutations exhibit inhibitory effects on wild-type p53 activity. More importantly, these mutations also demonstrate gain-of-function (GOF) activities characterized by increased metastasis, poor prognosis, and drug resistance. To better understand the activities by which TP53 mutations, identified in Li-Fraumeni syndrome, contribute to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…These two clusters were not characterized by the differences in histological type, developmental origin, TP53 genotype proportion, the proportion of hotspot mutations. There have been several reports on the relationship between the type of GOF and the tumor spectrum in which they occur 46 , 47 . The results of the present study were consistent with previous reports, with a higher percentage of GOF with hotspot mutations, R249 in LIHC 48 , 49 and R273 in LGG 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…These two clusters were not characterized by the differences in histological type, developmental origin, TP53 genotype proportion, the proportion of hotspot mutations. There have been several reports on the relationship between the type of GOF and the tumor spectrum in which they occur 46 , 47 . The results of the present study were consistent with previous reports, with a higher percentage of GOF with hotspot mutations, R249 in LIHC 48 , 49 and R273 in LGG 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…A portion of these are hotspot missense mutations. Their pathogenetic significance is not fully understood, but reports from other tumour types suggest that such single nucleotide variants constitute gain-of-function or separationof-function mutations [9][10][11][12][13][14][15]. The latter implies that while the tumour suppressor activity of wild-type TP53 is lost, mutant p53 reactivates parts of the TP53 pathway that are important for cancer cell survival and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental studies including systematic screens of synthetically generated variant libraries [ 9 ] reported distinct functional impact of different TP53 mutation types including LOF, DN impact, and GOF [ 47 ]. Furthermore, studies of TP53 germline mutations in animal models and cohorts of Li-Fraumeni syndrome patients revealed earlier cancer onset for specific TP53 mutations [ 47 50 ]. By contrast, in the current study in a large pan-cancer cohort of human tumors, virtually no significant gene expression changes between different TP53 mutation types were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental studies including systematic screens of synthetically generated variant libraries [9] reported distinct functional impact of different TP53 mutation types including LOF, DN impact, and GOF [47]. Furthermore, studies of TP53 germline mutations in animal models and cohorts of Li-Fraumeni syndrome patients revealed earlier cancer onset for specific TP53 mutations [47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%